Network structure of ICD-11 adjustment disorder: a cross-cultural comparison of three African countries. (October 2021) - Levin, Yafit; Bachem, Rahel; Karatzias, Thanos; Shevlin, Mark; Maercker, Andreas; Ben-Ezra, Menachem
Abstract : Background: Adjustment disorder is one of the most widespread mental disorders worldwide. In ICD-11, adjustment disorder is characterised by two main symptom clusters: preoccupation with the stressor and failure to adapt. A network analytic approach has been applied to most ICD-11 stress-related disorders. However, no study to date has explored the relationship between symptoms of adjustment disorder using network analysis. Aims: We aimed to explore the network structure of adjustment disorder symptoms and whether its structure replicates across questionnaire versions and samples. Method: A network analysis was conducted on adjustment disorder symptoms as assessed by the Adjustment Disorder–New Module (ADNM-8) and an ultra-brief version (ADNM-4) using data from 2524 participants in Nigeria ( n = 1006), Kenya ( n = 1018) and Ghana ( n = 500). Results: There were extensive connections between items across all samples in both ADNM versions. Results highlight that preoccupation symptoms seem to be more prominent in terms of edges strengths (i.e. connections) and had the highest centrality in all networks across samples and ADNM versions. Comparisons of network structure invariance revealed one difference between Nigeria and Ghana in both ADNM versions. Importantly, the ADNM-8 global strength was similar in all networks whereas in the ADNM-4 Kenya had a higher global strength score compared with Nigeria Conclusions: Results provide evidence of the coherence of adjustment disorder in ICD-11 as assessed by the ADNM questionnaire. The prominence of preoccupation symptoms in adjustment disorder highlights a possible therapeutic target to alleviate distress. There is a need to further replicate the network structure of adjustment disorder in non-African samples.